THE EFFECT OF GIVING DIFFERENT TYPES OF NATURAL FEED ON THE ABSOLUTE LENGTH GROWTH OF GALAXY RASBORA FISH (DANIO MARGARITATUS) SIZE 1.5-2 CM IN EXPERIMENTAL TANKS - Mahliana, Alika; Muhajir, Muhajir; Hayati, Nurul (Jurnal Perikanan Unram, 2025)
Rasbora galaxy (Danio margaritatus) is a type of freshwater ornamental fish that has a fairly high economic value and is in great demand in the international market. This fish is included in the omnivorous group of animals that tend to be carnivorous and can consume natural feed or commercial feed. Natural feed has advantages including very high nutritional content, easy to obtain and cheaper prices when compared to commercial feed. The types of natural feed that can potentially be consumed by rasbora galaxy fish measuring 1.5-2 cm are Tubifex sp), Artemia sp and Daphnia sp. The purpose of this study was to determine the effect of providing different types of natural feed on the absolute length growth of rasbora galaxy fish (Danio margaritatus) measuring 1.5-2 cm in experimental tanks. This study used an experimental method with a Completely Randomized Design (CRD) consisting of 3 treatments and 9 replications. The treatment in this study was in the form of providing different types of natural feed. Treatment A; Tubifex natural feed, treatment B; Artemia sp natural feed and treatment C; Daphnia sp natural feed. The test animals used 1.5 - 2 cm galaxy rasbora fish with an average weight of 0.5 g/tail and an average initial length of 1.5 cm. The stocking density was 15 fish/liter, the experimental media used fresh water with a volume of 3 liters/tank. The results showed that treatment A gave the best results for the absolute length growth of 1.5 - 2 cm galaxy rasbora fish of 0.7 cm/tail. Water quality data obtained water temperature ranged from 26.0-27.0 0C, acidity levels ranged from 6.9-7.2 and dissolved oxygen ranged from 4.5 - 5.0 ppm.”